Variability of the elements of spring barley yield structure depending on the hydrothermal conditions of vegetation - O. V. Levakova (Аграрная наука Евро-Северо-Востока, 2022)
The purpose of the research is to identify the main elements of the crop structure that affect the productivity of spring barley in different weather conditions in the Ryazan region. Field studies were carried out in the nursery of the competitive variety trial in 2017-2021 on dark gray forest heavy loam soil. The best zoned double-row varieties of spring barley (Yaromir, Nadezhny, Znatny, Raphael, Lyuboyar) and 4 promising lines were used as the object of research. It has been established that there is a relationship between the elements of the structure of the spring barley yield: the formation of one of the elements can be compensated by a more significant development of the other. In conditions of severe drought (НТС = 0.58-0.70), the greatest positive correlation of yield with the length of the ear (r = +0.437) and the number of grains in the ear (r = +0.279) was revealed. In arid conditions (НТС = 0.75-0.85), the number of plants before harvesting (r = +0.335) and the number of productive stems (r = +0.437) had the greatest impact on the yield. During the moisty year (НТС = 1.36), the productivity of barley was significantly affected by a set of indicators of structural elements: plant height (r = +0.890), grain weight from the ear (r = +0.810), the number of grains in the ear (r = +0.806), ear length (r = +0.774) and the mass of 1000 grains (r = +0.640). When analyzing the elements of the crop structure, a significant dependence (r = +0.674) was established between the length of the ear and the number of grains in it. A negative correlation has been established between the productive bushiness of plants and the mass of 1000 grains, between the number of productive stems and the mass of grain from the ear. It has been found out that the slightly varying traits include the number of grains in the ear (Cv = 4.8%) and the length of the ear (Cv = 9.6%). It has been revealed that the yield of the studied varieties and promising lines has a low variation over the years of Cv = 8.8%, which indicates to the effectiveness of breeding work on developing barley varieties with high and stable yields.